The vulnerable microcirculation in the critically ill pediatric patient. Issue 1 (December 2016) - Kuiper, J.; Tibboel, D.; Ince, C.
Abstract In neonates, cardiovascular system development does not stop after the transition from intra-uterine to extra-uterine life and is not limited to the macrocirculation. The microcirculation (MC), which is essential for oxygen, nutrient, and drug delivery to tissues and cells, also develops. Developmental changes in the microcirculatory structure continue to occur during the initial weeks of life in healthy neonates. The physiologic hallmarks of neonates and developing children make them particularly vulnerable during critical illness; however, the cardiovascular monitoring possibilities are limited compared with critically ill adult patients. Therefore, the development of non-invasive methods for monitoring the MC is necessary in pediatric critical care for early identification of impending deterioration and to enable the initiation and titration of therapy to ensure cell survival. To date, the MC may be non-invasively monitored at the bedside using hand-held videomicroscopy, which provides useful information regarding the microcirculation. There is an increasing number of studies on the MC in neonates and pediatric patients; however, additional steps are necessary to transition MC monitoring from bench to bedside. The recently introduced concept of hemodynamic coherence describes the relationship between changes in the MC and macrocirculation. The loss of hemodynamic coherence may result in a depressed MC despite an improvement in the macrocirculation, which represents a condition associated with adverse outcomes. In the pediatric intensive care unit, the concept of hemodynamic coherence may function as a framework to develop microcirculatory measurements towards implementation in daily clinical practice.